Sleep Disorders Associated With Alzheimer's Disease: A Perspective - Brzecka, Anna; Leszek, Jerzy; Ashraf, Ghulam Md; Ejma, Maria; Ávila-Rodriguez, Marco F.; Yarla, Nagendra S.; Tarasov, Vadim V.; Chubarev, Vladimir N.; Samsonova, Anna N.; Barreto, George E.; Aliev, Gjumrakch (Frontiers in Neuroscience, 2018)
Sleep disturbances, as well as sleep-wake rhythm disturbances, are typical symptoms of Alzheimer’s disease (AD) that may precede the other clinical signs and diagnosis of this neurodegenerative disease. Here, we describe clinical picture of sleep disorders in AD and the relation between sleep disorders and both cognitive impairment and poor prognosis of the disease. There are difficulties of the diagnosis of sleep disorders based on sleep questionnaires, polysomnography or actigraphy in the AD patients. Typical disturbances of the neurophysiological sleep architecture in the course of the AD include deep sleep and paradoxical sleep deprivation. Among sleep disorders occurring in patients with AD, the most frequent disorders are sleep breathing disorders – mainly obstructive sleep apnea (OSA) syndrome and restless legs syndrome/periodic legs movements’ syndrome. Sleep disorders may influence circadian fluctuations of the concentrations of amyloid-β in the interstitial brain fluid and in the cerebrovascular fluid related to the glymphatic brain system and production of the amyloid-β. There is accumulating evidence suggesting that disordered sleep contributes to cognitive decline and the development of AD pathology. In this mini-review, we highlight and discuss the association between sleep disorders and AD.